Friction material composition, friction material, and friction member
Patent Information
- Application Number
- JP2023139760
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0027】 本発明によれば、環境や人体に対する有害性が低い組成でありながら、制動時にPM10、PM2.5等の微細な摩耗粉塵の発生量が少ないロースチール材を形成することができる、摩擦材組成物、並びに該摩擦材組成物を用いた摩擦材及び摩擦部材を提供することができる。
Smart Images

Figure 2025033786000001 
Figure 2025033786000002 
Figure 2025033786000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a friction material composition, and a friction material and a friction member using the friction material composition. [Background technology]
[0002] Friction materials used in brakes such as disc brakes and drum brakes that constitute the braking devices of various vehicles and industrial machines are required to have a large and stable friction coefficient, excellent wear resistance, and low attack on mating materials. Such friction materials are classified into three types: semi-metallic materials that contain steel-based fibers such as steel fibers and stainless steel fibers as a fiber base material at a ratio of 30% to less than 60% by mass; low-steel materials that contain steel-based fibers at a ratio of 10% to less than 30% by mass; and NAO (Non-Asbestos-Organic) materials that do not contain steel-based fibers. However, friction materials that contain a small amount of steel-based fibers are also classified as NAO materials.
[0003] In Japan and the United States, where comfort is emphasized, NAO materials are mainstream because they are less aggressive to mating materials and have an excellent balance between noise and wear resistance. Meanwhile, in Europe, low-steel materials are mainstream because friction materials that are effective under all conditions, such as high-speed braking on the Autobahn, are preferred.
[0004] Copper fibers and copper powder are generally blended into the composition used for the friction material (hereinafter referred to as "friction material composition"). The first role of copper is to impart thermal conductivity to the friction material. Since copper has high thermal conductivity, it can diffuse heat generated during braking from the friction surface, thereby reducing wear of the friction material caused by excessive temperature rise and suppressing vibration during braking. The second role of copper is to protect the friction surface during high-temperature braking. Due to the malleability of copper, it extends to the surface of the friction material during braking and forms a coating. In addition, copper transfers to the surface of the mating material and forms an adhesive coating (hereinafter referred to as "transfer film"). These act as protective films to reduce wear of the friction material during high-temperature braking and enable the friction material to exhibit a stable friction coefficient. However, friction materials that contain copper generate wear particles during braking, which may pollute rivers, lakes, and oceans. As a result, state laws have gone into effect in the U.S. states of California and Washington that will prohibit the sale and installation in new vehicles of friction materials that contain 0.5% or more by mass of copper from 2025 onwards.
[0005] Therefore, in NAO materials, titanates such as potassium titanate, lithium potassium titanate, and magnesium potassium titanate have been attracting attention as components that play a role in the transfer film other than copper. For example, a friction material composition containing lithium potassium titanate and graphite (Patent Document 1), a friction material composition containing two or more types of titanates and ceramic fibers (Patent Document 2), and a friction material composition containing a titanate with a tunnel crystal structure and a titanate with a layered crystal structure (Patent Document 3) have been proposed. In addition, metal sulfides are widely used in NAO materials for the purpose of stabilizing the friction coefficient during high-speed and high-load braking (see, for example, Patent Document 4 (paragraph number 0032)). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2012 / 066968 [Patent Document 2] JP 2015-059143 A [Patent Document 3] JP 2015-147913 A [Patent Document 4] International Publication No. 2017 / 183155 Summary of the Invention [Problem to be solved by the invention]
[0007] Even in low-steel materials, metal sulfides are used as essential ingredients to prevent Fe-Fe adhesion between the mating material (disc rotor, etc.) and the steel fibers, despite the fact that they are highly harmful to the human body. In particular, low-steel materials tend to contain more metal sulfides than NAO materials.
[0008] In addition, while low-steel materials have a large coefficient of friction and good stability of effectiveness, they are highly aggressive to mating materials, and therefore dirt on wheels caused by wear dust from friction materials and mating materials (such as disc rotors) is a problem. Therefore, it is necessary not only to reduce the copper content in low-steel materials, but also to reduce the amount of wear dust during braking. One method of reducing wear dust is to reduce the load on friction brakes, and one of the methods is the popularization of regenerative braking by converting cars into electric vehicles (EVs) and hybrids. However, EVs are heavier than gasoline-powered cars, and the level of regeneration of regenerative braking is not uniform depending on the model and driving conditions, so the effect of regenerative braking in reducing wear dust is not sufficient.
[0009] Additionally, the European Commission has officially decided that brake emissions will be regulated by Euro 7 from 2025 onwards, and proposed limits for particulate matter (PM) have been published. The proposed limits are set at 7 mg / km for PM10 emissions from vehicles from 2026, and 3 mg / km from 2035, which are extremely strict limits for low-steel materials. Furthermore, regulatory limits for PM2.5 and PN (number of PM) are also under discussion, with emphasis being placed on the particle size of wear dust. These regulations will have an impact around the world, and preparations are underway to introduce similar regulations in various countries in the future.
[0010] The present invention has been made in consideration of the above circumstances, and has an object to provide a friction material composition that can form a low-steel material that generates little fine wear dust such as PM10 (particulate matter having an aerodynamic diameter of 10 μm or less) and PM2.5 (particulate matter having an aerodynamic diameter of 2.5 μm or less) during braking, while having a composition that is low in harmfulness to the environment and human body, and a friction material and friction member that use the friction material composition. [Means for solving the problem]
[0011] The present invention provides the following friction material composition, and a friction material and a friction member using the friction material composition.
[0012] Item 1: A friction material composition comprising a binder, steel-based fibers, titanate, and a carbon-based solid lubricant, the content of the steel-based fibers in the friction material composition is 10% by mass or more and less than 30% by mass, based on 100% by mass of the total amount of the friction material composition, the content of copper in the friction material composition is less than 0.5% by mass in terms of elemental copper, based on 100% by mass of the total amount of the friction material composition, the friction material composition contains two or more types of titanates, and the friction material composition is substantially free of metal sulfides.
[0013] Item 2. The friction material composition according to item 1, wherein the total content of the two or more types of titanates in the friction material composition is 5% by mass or more and 35% by mass or less, relative to 100% by mass of the total amount of the friction material composition.
[0014] Item 3. The friction material composition according to item 1 or 2, wherein the two or more kinds of titanates include at least a non-porous titanate (A) and a porous titanate (B).
[0015] Item 4. The friction material composition according to item 3, wherein the titanate (A) is a titanate having a layered crystal structure.
[0016] Item 5. The friction material composition according to item 3 or 4, wherein the titanate (A) has an average particle size of 0.1 μm or more and 50 μm or less.
[0017] Item 6. The friction material composition according to any one of Items 3 to 5, wherein the titanate (B) is a titanate having a tunnel-shaped crystal structure.
[0018] Item 7. The friction material composition according to any one of Items 3 to 6, wherein the titanate (B) has an average particle size of 50 μm or more and 200 μm or less.
[0019] Item 8. The friction material composition according to any one of Items 3 to 7, wherein a mass ratio of the titanate (A) to the titanate (B) (titanate (A) / titanate (B)) is 0.1 or more and 12.0 or less.
[0020] Item 9. The friction material composition according to any one of items 1 to 8, wherein the content of the carbon-based solid lubricant in the friction material composition is 0.1% by mass or more and less than 15% by mass, relative to 100% by mass of the total amount of the friction material composition.
[0021] Item 10. The friction material composition according to any one of Items 1 to 9, wherein a mass ratio of the two or more kinds of titanates to the carbon-based solid lubricant (titanate / carbon-based solid lubricant) is 2.0 or more and 6.0 or less.
[0022] Item 11. The friction material composition according to any one of Items 1 to 10, wherein the carbon-based solid lubricant is graphite.
[0023] Item 12. The friction material composition according to any one of Items 1 to 11, wherein the carbon-based solid lubricant has an average particle size of 10 μm or more and 1000 μm or less.
[0024] Item 13. The friction material composition according to any one of items 1 to 12, wherein the steel fibers have an average fiber length of 0.1 mm or more and 5 mm or less.
[0025] Item 14. A friction material which is a molded product of the friction material composition according to any one of items 1 to 13.
[0026] Item 15. A friction member comprising the friction material according to item 14. Effect of the Invention
[0027] According to the present invention, it is possible to provide a friction material composition capable of forming a low-steel material that has a composition that is less harmful to the environment and human body and that generates less fine wear dust such as PM10 and PM2.5 during braking, as well as a friction material and a friction member that use the friction material composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Hereinafter, an example of a preferred embodiment of the present invention will be described. However, the following embodiment is merely an example, and the present invention is not limited to the following embodiment.
[0029] <1.Friction material composition> The friction material composition of the present invention is characterized in that, in the friction material composition containing a binder, a steel-based fiber, a titanate, and a carbon-based solid lubricant, the content of the steel-based fiber in the friction material composition is 10% by mass or more and less than 30% by mass relative to 100% by mass of the total amount of the friction material composition, the content of copper in the friction material composition is less than 0.5% by mass as copper element relative to 100% by mass of the total amount of the friction material composition, the friction material composition contains two or more types of titanates, and the friction material composition is substantially free of metal sulfides. In addition, the friction material composition of the present invention can further contain other materials as necessary. In this specification, the "friction material composition" refers to a composition used for a friction material.
[0030] In the present invention, the content of copper in the friction material composition is less than 0.5% by mass as copper element relative to 100% by mass of the total amount of the friction material composition, and preferably the friction material composition does not contain a copper component. In this specification, "the friction material composition does not contain a copper component" means that none of copper fibers, copper powder, and copper-containing alloys (brass or bronze, etc.) and compounds are blended as raw materials of the friction material composition. The friction material composition of the present invention has a copper content of less than 0.5% by mass as copper element relative to 100% by mass of the total amount of the friction material composition, and preferably does not contain a copper component, so that it can reduce harmfulness to the environment (environmental load) compared to conventional friction material compositions.
[0031] In the present invention, the friction material composition does not substantially contain metal sulfides. In this specification, "metal sulfide" refers to sulfur-based solid lubricants such as antimony trisulfide, molybdenum disulfide, tin sulfide, iron sulfide, zinc sulfide, bismuth sulfide, and tungsten disulfide. In addition, in this specification, "the friction material composition does not substantially contain metal sulfides" means that metal sulfides are not intentionally blended into the friction material composition, and does not contain metal sulfides in the friction material composition except when metal sulfides are mixed into the friction material composition as trace impurities. In particular, the content of metal sulfides is preferably less than 0.1% by mass with respect to the total amount of the friction material composition (100% by mass), and it is more preferable that the friction material composition does not contain any metal sulfides at all. Since the friction material composition of the present invention does not substantially contain metal sulfides, it is less harmful to the human body and can be expected to have an effect of inhibiting rusting of the rotor.
[0032] The friction material composition of the present invention has the above-mentioned overall configuration, and while it has a composition that is low in harmfulness to the environment and human body, it is possible to form a low-steel material that not only reduces the amount of wear of friction materials (such as disc brake pads) and mating materials (such as disc rotors) during braking, but also generates little fine wear dust such as PM10 and PM2.5.
[0033] Hereinafter, each of the materials constituting the friction material composition of the present invention will be described in detail.
[0034] (1-1.Binding material) The binder binds together the steel fibers, titanates, etc. contained in the friction material composition and imparts strength to the friction material. There are no particular limitations on the binder used in the friction material composition of the present invention, and any thermosetting resin that is usually used as a binder for friction materials can be used.
[0035] Examples of the thermosetting resin include phenolic resin; elastomer-dispersed phenolic resin such as acrylic elastomer-dispersed phenolic resin and silicone elastomer-dispersed phenolic resin; modified phenolic resin such as acrylic-modified phenolic resin, silicone-modified phenolic resin, cashew-modified phenolic resin, epoxy-modified phenolic resin, and alkylbenzene-modified phenolic resin; formaldehyde resin; melamine resin; epoxy resin; acrylic resin; aromatic polyester resin; urea resin, etc. One of these may be used alone, or two or more may be used in combination. Among these, from the viewpoint of further improving the heat resistance, moldability, and friction characteristics of the friction material, the thermosetting resin is preferably a phenolic resin (straight phenolic resin) or a modified phenolic resin.
[0036] The content of the binder in the friction material composition is preferably 5% by mass or more, more preferably 6% by mass or more, and preferably 20% by mass or less, more preferably 15% by mass or less, based on 100% by mass of the total amount of the friction material composition. By setting the content of the binder within the above range, an appropriate amount of the binder is filled into the gaps of the blended materials, and when the material is used as a friction material, even better friction characteristics can be obtained.
[0037] (1-2. Steel-based fibers) Examples of the steel-based fibers include steel fibers and stainless steel fibers, with steel fibers being preferred.
[0038] Examples of steel fibers include straight fibers obtained by chatter vibration cutting and curled fibers obtained by cutting long fibers. Straight fibers are linear fibers. Curled fibers, on the other hand, have a curved shape, and include simple arcs, undulating fibers, and spiral or volute fibers.
[0039] Among them, the steel fibers are preferably curled fibers from the viewpoint of reducing the amount of fiber that falls off the friction material on the friction surface and more reliably maintaining the friction characteristics during high-temperature braking. Furthermore, it is more preferable that the curled fibers include a portion having a radius of curvature of 100 μm or less. In this case, the fibers are more firmly fixed to the friction material, and the friction material is less likely to fall off the friction surface.
[0040] The average fiber length of the steel-based fibers is preferably 5 mm or less, more preferably 2.5 mm or less, from the viewpoint of further improving the wear resistance at high temperatures when used as a friction material. Also, the average fiber length of the steel-based fibers is preferably 0.1 mm or more, more preferably 0.5 mm or more, and even more preferably 1.1 mm or more, from the viewpoint of further improving the reinforcing property when used as a friction material. In consideration of these, the average fiber length of the steel-based fibers is preferably 0.1 mm to 5 mm, more preferably 0.5 mm to 2.5 mm, and even more preferably 1.1 mm to 2.5 mm.
[0041] The average fiber diameter of the steel-based fibers is preferably 300 μm or less, more preferably 100 μm or less, from the viewpoint of further suppressing brake vibration at high temperatures when used as a friction material. Also, the average fiber diameter of the steel-based fibers is preferably 10 μm or more, more preferably 30 μm or more, from the viewpoint of further preventing the steel-based fibers from falling off when used as a friction material. Taking these into consideration, the average fiber diameter of the steel-based fibers is preferably 10 μm to 300 μm, more preferably 30 μm to 100 μm.
[0042] The average fiber length and average fiber diameter of the steel-based fibers can be confirmed using a microscope, etc. For example, they can be the average values of 30 steel-based fibers observed using a microscope.
[0043] The content of the steel fibers is 10 mass% or more, preferably 12 mass% or more, and more preferably 15 mass% or more, relative to 100 mass% of the total amount of the friction material composition, and is less than 30 mass%, preferably 28 mass% or less, and more preferably 25 mass% or less.
[0044] (1-3. Titanates) The friction material composition of the present invention contains two or more types of titanates.
[0045] Examples of titanates include potassium hexatitanate, sodium hexatitanate, potassium octatitanate, magnesium potassium titanate, lithium potassium titanate, etc. From the viewpoint of further reducing fine wear dust when used as a friction material, it is preferable that one of the two or more titanates is magnesium potassium titanate.
[0046] Titanates have crystal structures such as a layered crystal structure, a tunnel-shaped crystal structure, etc. From the viewpoint of further reducing fine wear dust when used as a friction material, it is preferable that one of the two or more types of titanates is a titanate having a layered crystal structure.
[0047] In the present invention, the two or more kinds of titanates preferably include at least a non-porous titanate (A) and a porous titanate (B). In addition, the titanate (A) and the titanate (B) are preferably non-fibrous particles from the viewpoint of working environment. In particular, it is preferable that the titanate (A) is a non-porous particle and the titanate (B) is a porous particle. In this case, when used as a friction material, the amount of fine wear dust generated can be further reduced.
[0048] In this specification, the term "non-fibrous particle" refers to a particle in which the longest side of the rectangular parallelepiped circumscribing the particle and having the smallest volume (circumscribing rectangular parallelepiped) is the major axis L, the second longest side is the minor axis B, and the shortest side is the thickness T (B>T), with L / B being 5 or less.
[0049] Examples of the particle shape of the non-porous particles include spherical (including those with slight irregularities on the surface and those with a roughly spherical shape such as an elliptical cross section), columnar (including those with a roughly columnar overall shape such as a rod, cylinder, prism, strip, roughly cylindrical, roughly strip), plate, block, shapes with multiple protrusions (amoeba, boomerang, cross, confetti, etc.), and irregular shapes. These particle shapes may be used alone or in combination with a plurality of shapes. Among these, plate-shaped particles are preferred as non-porous particles.
[0050] Incidentally, "having multiple convex portions" refers to a shape that has convex portions in two or more directions when projected onto a plane, unlike at least a normal polygon, circle, ellipse, etc. Specifically, this convex portion refers to a portion that corresponds to a protruding portion when a polygon, circle, ellipse, etc. (basic figure) is fitted onto a photograph (projection drawing) taken with a scanning electron microscope (SEM).
[0051] Examples of the shape of the porous particles include a particle shape in which a plurality of columnar particles are irregularly oriented and integrated, a particle shape in which titanate crystal grains are bonded by sintering and / or fusion, etc. In addition, the porous particles are preferably spherical particles (including those with slight irregularities on the surface and those with a cross section that is approximately spherical, such as an elliptical shape).
[0052] These various particle shapes can be freely controlled by the production conditions, particularly the raw material composition, the firing conditions, etc. Furthermore, these various particle shapes can be analyzed, for example, by observation with a scanning electron microscope (SEM).
[0053] In the present invention, it is preferred that the non-porous titanate (A) is a titanate having a layered crystal structure, and the porous titanate (B) is a titanate having a tunnel-shaped crystal structure, in which case the amount of fine wear dust generated can be further reduced when used as a friction material.
[0054] The formula of the titanate having a layered crystal structure is, for example, xM y Ti (2-y) O4 (wherein A is one or more alkali metals other than lithium (Li), M is one or more selected from Li, Mg, Zn, Ga, Ni, Cu, Fe, Al, and Mn, x is a number of 0.5 to 1.0, and y is a number of 0.25 to 1.0), 0.1~0.8 Li 0.2~0.4 Ti 1.6~1.8 O 3.65~3.95 [wherein A is one or more alkali metals other than Li], A 0.2~0.8 Mg 0.3~0.5 Ti 1.5~1.7 O 3.7~3.95 [wherein A is one or more alkali metals other than Li], A 0.5~0.7 Li (0.27-x) M y Ti (1.73-z) O 3.85~3.95 [wherein A is one or more alkali metals other than Li, M is one or more selected from Mg, Zn, Ga, Ni, Cu, Fe, Al, and Mn (however, when there are two or more, combinations of ions with different valences are excluded), and x and z are, when M is a divalent metal, x=2y / 3, z=y / 3, and when M is a trivalent metal, x=y / 3, z=2y / 3, and y is 0.004≦y≦0.4]. The composition formula of titanates having a layered crystal structure is preferably A x M y Ti (2-y) O4 (wherein A is one or more alkali metals other than Li, M is one or more selected from Li, Mg, Zn, Ga, Ni, Cu, Fe, Al, and Mn, x is a number from 0.5 to 1.0, and y is a number from 0.25 to 1.0), A 0.5~0.7 Li 0.27 Ti 1.73 O 3.85~3.95 [wherein A is one or more alkali metals other than Li], and A 0.2~0.7 Mg 0.40 Ti 1.6 O 3.7~3.95 In the formula, A is at least one selected from the group consisting of one or more alkali metals other than Li.
[0055] Examples of the alkali metal other than lithium (Li) include sodium, potassium, rubidium, cesium, francium, etc. Among them, the alkali metal other than lithium (Li) is preferably sodium or potassium because it is economically advantageous.
[0056] Specific examples of titanates with layered crystal structures include K 0.8 Li 0.27 Ti 1.73 O4 (Lithium potassium titanate), K 0.7 Li 0.27 Ti 1.73 O 3.95 (Lithium potassium titanate), K 0.6 Li 0.27 Ti 1.73 O 3.9 (Lithium potassium titanate), K 0.4 Li 0.27 Ti 1.73 O 3.8 (Lithium potassium titanate), K 0.3 Li 0.27 Ti 1.73 O 3.75 (Lithium potassium titanate), K 0.8 Mg 0.4 Ti 1.6 O4 (Magnesium potassium titanate), K 0.7 Mg 0.4 Ti 1.6 O 3.95 (Magnesium potassium titanate), K 0.5 Mg 0.4 Ti 1.6 O 3.85 (Magnesium potassium titanate), K 0.4 Mg 0.4 Ti 1.6 O 3.8 (Magnesium potassium titanate), K 0.3 Mg 0.4 Ti 1.6 O 3.75 (Magnesium potassium titanate), K 0.7 Li 0.13 Mg 0.2 Ti 1.67 O 3.96 (Lithium magnesium potassium titanate), K0.7 Li 0.24 Mg 0.04 Ti 1.72 O 3.95 (Lithium magnesium potassium titanate), K 0.7 Li 0.13 Fe 0.4 Ti 1.47 O 3.95 (lithium iron potassium titanate), etc.
[0057] The formula of the tunnel-shaped crystal structure titanate is, for example, A2Ti n O (2n+1) [In the formula, A is one or more alkali metals other than Li, and n is a number from 2 to 11], A (2+y) Ti (6-x) M x O (13+y / 2-(4-z)x / 2) [wherein A is one or more alkali metals other than Li, M is one or more selected from Li, Mg, Zn, Ga, Ni, Cu, Fe, Al, and Mn, z is the valence of element M and is an integer of 1 to 3, x is 0.05≦x≦0.5, and y is 0≦y≦(4-z)x], and preferably A2Ti n O (2n+1) [wherein A is one or more alkali metals other than Li, and n is a number from 2 to 11], and more preferably ATi n O (2n+1) [wherein A is one or more alkali metals other than Li, and n is a number from 4 to 9], and more preferably KTi n O (2n+1) [wherein n is a number from 4 to 9] and Na2Ti n O (2n+1) [wherein n is a number from 4 to 8].
[0058] A specific example of a titanate with a tunnel crystal structure is K2Ti 4.8 O 10.6 (4.8 Potassium titanate), K2Ti6O 13 (Potassium hexatitanate), K2Ti 6.1 O 13.2 (6.1 Potassium Titanate), K2Ti 7.9 O 16.8 (7.9 Potassium titanate), K2Ti8O17 (potassium titanate octahydrate), K2Ti 10.9 O 22.8 (10.9 Potassium titanate), Na2Ti6O 13 (Sodium hexatitanate), Na2Ti8O 17 (Sodium titanate 8), K 2.15 Ti 5.85 Al 0.15 O 13.0 (Potassium aluminum titanate), K 2.20 Ti 5.60 Al 0.40 O 12.9 (Potassium aluminum titanate), K 2.20 Ti 5.90 Li 0.10 O 12.95 (lithium potassium titanate), etc.
[0059] The average particle size of the titanate (A) is preferably 0.1 μm or more, more preferably 1 μm or more, and is preferably 50 μm or less, more preferably 35 μm or less. When the average particle size of the titanate (A) is within the above range, the amount of fine wear dust generated when used as a friction material can be further reduced.
[0060] The average particle size of the titanate (B) is preferably 50 μm or more, and preferably 200 μm or less, more preferably 100 μm or less, and further preferably 85 μm or less. When the average particle size of the titanate (B) is within the above range, the amount of fine wear dust generated when used as a friction material can be further reduced.
[0061] In this specification, unless otherwise specified, the average particle size refers to the particle size at 50% cumulative volume in the particle size distribution measured by a laser diffraction method (D 50 ) This D 50 is the particle size at which the cumulative value reaches 50% when the particle size distribution is calculated on a volume basis and the number of particles is counted from the smallest particle size on a cumulative curve with the total volume set to 100%.
[0062] Hereinafter, titanic acid (A) and titanate (B) may be collectively referred to as titanate.
[0063] The specific surface area of the titanate is preferably 0.1 m 2 / g or more, more preferably 0.2m 2 / g or more, more preferably 0.5m 2 / g or more, preferably 10m 2 / g or less, more preferably 9m 2 / g or less, more preferably 8m 2 / g or less. The specific surface area can be measured in accordance with JIS Z8830.
[0064] The alkali metal ion elution rate of the titanate is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, even more preferably 0.1 mass% or more, and is preferably 15 mass% or less, more preferably 10 mass% or less, even more preferably 6 mass% or less.
[0065] In the curing reaction of novolac phenolic resin, which is an example of a binder used in a friction material composition, the curing accelerator, for example, hexamethylenetetramine, opens its ring and bonds with the hydroxyl group in the novolac phenolic resin, starting the curing reaction. However, when alkali metal ions are present in the friction material composition, the alkali metal ions and the hydrogen ions in the hydroxyl group in the novolac phenolic resin undergo an ion exchange reaction, which is thought to inhibit the bond between hexamethylenetetramine (curing accelerator) and the novolac phenolic resin (thermosetting resin) (curing inhibition). On the other hand, it is thought that the wear and destruction of the friction material due to braking causes an alkali component derived from titanate to elute onto the friction surface.
[0066] Therefore, by setting the alkali metal ion elution rate to the above upper limit or less, it is possible to prevent the curing of the thermosetting resin from being inhibited during hot and pressure molding, and as a result, when the friction material is used, it is possible to further improve the crack resistance at high temperature and high load. Furthermore, by setting the alkali metal ion elution rate to the above lower limit or more, it is possible to suppress rusting of the mating material (such as a disk rotor) even if the friction material of the present invention is left unused for a long period of time after braking. In other words, by setting the alkali metal ion elution rate within the above range, it is possible to achieve both the crack resistance of the friction material and the suppression of rusting of the mating material (such as a disk rotor).
[0067] In this specification, the alkali metal ion elution rate refers to the mass ratio of alkali metal ions eluted from a measurement sample such as a titanate in water at 80°C.
[0068] In addition, in the case of titanate, a treatment layer made of a surface treatment agent may be formed on the surface of the titanate for the purpose of further improving dispersibility and adhesion to the binder.
[0069] The surface treatment agent is not particularly limited, but includes silane coupling agents, titanium coupling agents, etc. Among these, silane coupling agents are preferred, and amino-based silane coupling agents, epoxy-based silane coupling agents, or alkyl-based silane coupling agents are more preferred. The above surface treatment agents may be used alone or in combination of two or more.
[0070] Examples of amino-based silane coupling agents include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-ethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, and N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane.
[0071] Examples of epoxy-based silane coupling agents include 3-glycidyloxypropyl(dimethoxy)methylsilane, 3-glycidyloxypropyltrimethoxysilane, diethoxy(3-glycidyloxypropyl)methylsilane, triethoxy(3-glycidyloxypropyl)silane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0072] Examples of alkyl silane coupling agents include methyltrimethoxysilane, dimethyldimethoxysilane, trimethylmethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, n-propyltrimethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, cyclohexylmethyldimethoxysilane, n-octyltriethoxysilane, and n-decyltrimethoxysilane.
[0073] A known surface treatment method can be used as a method for forming a treatment layer made of a surface treatment agent on the surface of the titanate. For example, a wet method can be used in which the surface treatment agent is dissolved in a solvent (e.g., water, alcohol, or a mixed solvent thereof) that promotes hydrolysis to prepare a solution, and the solution is sprayed onto the titanate.
[0074] The amount of the surface treatment agent used when treating the surface of the titanate is not particularly limited. In the case of a wet method, for example, a solution of the surface treatment agent may be sprayed so that the amount of the surface treatment agent is 0.1 to 20 parts by mass per 100 parts by mass of the titanate.
[0075] The titanate used in the present invention may be a granulated form obtained by treating the titanate with a surface treatment agent. The average particle size of the granular titanate is preferably 100 μm or more and preferably 200 μm or less.
[0076] Examples of the titanate include potassium hexatitanate such as TERRACESS JSL, TERRACESS JSL-R, TERRACESS DP-R, TERRACESS DP-A, and TERRACESS DP-AS manufactured by Otsuka Chemical Co., Ltd., TXAX-MA and TXAX-A manufactured by Kubota Corporation, and TOFIX-S and TOFIX-SNR manufactured by Toho Titanium Co., Ltd.; sodium hexatitanate such as TERRACESS DSR manufactured by Otsuka Chemical Co., Ltd.; potassium octatitanate such as TERRACESS TF-SS, TERRACESS TF-S, TERRACESS TF-L, and TERRACESS JP manufactured by Otsuka Chemical Co., Ltd.; magnesium potassium titanate such as TERRACESS PM and TERRACESS PS manufactured by Otsuka Chemical Co., Ltd.; and lithium potassium titanate such as TERRACESS L, TERRACESS L-SS, and TERRACESS JSM-M manufactured by Otsuka Chemical Co., Ltd.
[0077] The total content of the two or more titanates is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more, relative to 100% by mass of the total amount of the friction material composition, and is preferably 35% by mass or less, more preferably 33% by mass or less, and even more preferably 30% by mass or less. In consideration of these, the total content of the two or more titanates is preferably 5% by mass to 35% by mass, more preferably 10% by mass to 33% by mass, and even more preferably 20% by mass to 30% by mass. By setting the total content of the two or more titanates within the above range, when the friction material is used, the friction coefficient can be increased and fine wear dust can be further reduced.
[0078] The mass ratio of the two or more titanates to the steel-based fibers (titanate / steel-based fibers) is preferably 0.1 or more, more preferably 0.6 or more, even more preferably 0.8 or more, and is preferably 3.0 or less, more preferably 2.5 or less, even more preferably 2.0 or less. By setting the mass ratio of the two or more titanates to the steel-based fibers within the above range, the detachment of the steel-based fibers can be further suppressed when the friction material is used. The mass ratio of the two or more titanates to the steel-based fibers is the mass ratio of the total mass of the two or more titanates to the mass of the steel-based fibers.
[0079] The mass ratio of the two or more titanates to the binder (titanate / binder) is preferably 0.4 or more, more preferably 1.0 or more, even more preferably 1.3 or more, and is preferably 8.0 or less, more preferably 5.0 or less, even more preferably 3.0 or less. By setting the mass ratio of the two or more titanates to the binder within the above range, when the friction material is used, the amount of carbide present on the friction surface can be optimized, and the detachment of steel-based fibers can be further suppressed. The mass ratio of the two or more titanates to the binder is the mass ratio of the total mass of the two or more titanates to the mass of the binder.
[0080] In addition, when the two or more kinds of titanates are the titanate (A) and titanate (B) described above, the mass ratio of the titanate (A) to the titanate (B) (titanate (A) / titanate (B)) is preferably 0.1 or more, more preferably 0.5 or more, even more preferably 1.0 or more, and preferably 12.0 or less, more preferably 10.0 or less, even more preferably 5.0 or less. In consideration of these, the mass ratio of the titanate (A) to the titanate (B) is preferably 0.1 to 12.0, more preferably 0.5 to 10.0, even more preferably 1.0 to 5.0. By setting the mass ratio of the titanate (A) to the titanate (B) to the above range, the amount of fine wear dust generated when used as a friction material can be further reduced.
[0081] (1-4. Carbon-based solid lubricants) Examples of the carbon-based solid lubricant include synthetic graphite or natural graphite (graphite), flake graphite, phosphate-coated graphite, carbon black, petroleum coke, coal coke, activated carbon, elastic graphitized carbon, oxidized polyacrylonitrile fiber pulverized powder, etc. From the viewpoint of further increasing the thermal conductivity when used as a friction material, the carbon-based solid lubricant is preferably graphite, and more preferably synthetic graphite or natural graphite.
[0082] The content of the carbon-based solid lubricant is preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more, based on the total amount of the friction material composition (100% by mass), and is preferably less than 15% by mass, more preferably less than 10% by mass, and even more preferably less than 8% by mass. If the content of the carbon-based solid lubricant is equal to or more than the above lower limit, the friction material tends to have better wear resistance at high temperatures when used as a friction material. Also, if the content of the carbon-based solid lubricant is less than the above upper limit or equal to or less than the upper limit, the friction material tends to have better wear resistance at high temperatures when used as a friction material.
[0083] The average particle size of the carbon-based solid lubricant is not particularly limited, but is preferably 10 μm or more and 1000 μm or less. The carbon-based solid lubricant may be used alone, or may be used in combination of two or more types having different average particle sizes. If the average particle size of the carbon-based solid lubricant is equal to or more than the above lower limit, the thermal conductivity of the friction material is prevented from increasing excessively, and the friction heat is easily prevented from being transferred to the back plate side to cause vapor lock. If the average particle size of the carbon-based solid lubricant is equal to or less than the above upper limit, the thermal conductivity is improved, the hardening of the binder during the molding of the friction material is promoted, and the strength of the friction material tends to be improved.
[0084] The mass ratio of two or more kinds of titanates to the carbon-based solid lubricant (titanate / carbon-based solid lubricant) is preferably 2.0 or more, more preferably 3.0 or more, even more preferably 3.5 or more, and preferably 6.0 or less, more preferably 5.5 or less, even more preferably 5.0 or less. In consideration of these, the mass ratio of two or more kinds of titanates to the carbon-based solid lubricant is preferably 2.0 to 6.0, more preferably 3.0 to 5.5, even more preferably 3.5 to 5.0. By setting the mass ratio of two or more kinds of titanates to the carbon-based solid lubricant in the above range, the fade resistance when used as a friction material can be further improved. The mass ratio of two or more kinds of titanates to the carbon-based solid lubricant is the mass ratio of the total mass of two or more kinds of titanates to the mass of the carbon-based solid lubricant.
[0085] (1-5. Other materials) In addition to the above-mentioned binder, steel-based fiber, titanate, and carbon-based solid lubricant, the friction material composition of the present invention may contain other materials typically used in friction material compositions (such as a fibrous base material, an organic friction modifier, an inorganic friction modifier, a lubricant, a pH adjuster, and a filler) as necessary.
[0086] The content of the other materials in the friction material composition is preferably 20% by mass or more and preferably 80% by mass or less, based on 100% by mass of the total amount of the friction material composition.
[0087] (1-5-1. Fiber base material) The friction material composition of the present invention may further contain other fiber base materials in addition to the steel-based fibers. The other fiber base materials exhibit reinforcing properties in the friction material. Examples of the other fiber base materials include inorganic fibers, metal fibers, organic fibers, and carbon-based fibers. One of these may be used alone, or two or more may be used in combination.
[0088] When the friction material composition contains other fibrous base materials other than steel-based fibers, the content of the other fibrous base materials is preferably 0.1 mass % or more, and is preferably 40 mass % or less, more preferably 20 mass % or less, and even more preferably 10 mass % or less, relative to 100 mass % of the total amount of the friction material composition.
[0089] Examples of inorganic fibers include glass fibers, rock wool, ceramic fibers, biodegradable ceramic fibers, biodegradable mineral fibers, biosoluble fibers (such as SiO2-CaO-SrO fibers), wollastonite fibers, silicate fibers, mineral fibers, and the like. Of these, the inorganic fiber is preferably rock wool.
[0090] Examples of metal fibers include straight or curled metal fibers whose main component is a metal such as aluminum, iron, zinc, tin, titanium, nickel, magnesium, silicon, or other metal or alloy fibers (excluding steel-based fibers).
[0091] Examples of organic fibers include aromatic polyamide (aramid) fibers, fibrillated aramid fibers, acrylic fibers (homopolymer or copolymer fibers whose main raw material is acrylonitrile), fibrillated acrylic fibers, cellulose fibers, fibrillated cellulose fibers, and phenolic resin fibers.
[0092] Examples of carbon-based fibers include flame-retardant fibers, PAN-based carbon fibers, pitch-based carbon fibers, activated carbon fibers, and the like.
[0093] The other fiber base material is preferably an aramid fiber, since the other fiber base material is provided with appropriate water absorption properties so that moisture in the air can be easily absorbed inside the friction material, and the alkali component of the titanate can be easily eluted, and the rust prevention effect of the steel-based fiber can be expected.
[0094] From the viewpoint of further improving the heat resistance when used as a friction material, the other fiber base material is preferably a para-aramid fiber such as poly-p-phenylene terephthalamide.
[0095] From the viewpoint of further improving the moldability of the friction material and further improving the retention of the filler, the other fiber base material is preferably fibrillated aramid fiber (also called aramid pulp).
[0096] The specific surface area of the fibrillated aramid fibers is preferably 5 m 2 / g or more, preferably 25m 2 / g or less, more preferably 15m 2 The fiber length of the fibrillated aramid fibers is preferably 0.5 mm or more and preferably 1.2 mm or less.
[0097] When the friction material composition contains fibrillated aramid fibers, the content thereof is preferably 1 mass % or more, preferably 10 mass % or less, more preferably 8 mass % or less, and further preferably 6 mass % or less, based on 100 mass % of the total amount of the friction material composition. When the content of the fibrillated aramid fibers is equal to or more than the above lower limit, the crack resistance and wear resistance of the friction material when used as a friction material are improved, and when the content of the fibrillated aramid fibers is equal to or less than the above upper limit, deterioration of the crack resistance and wear resistance of the friction material due to uneven distribution of the fibrillated aramid fibers and other materials can be prevented.
[0098] When the friction material composition contains rock wool, the content is preferably 1 mass % or more, preferably 10 mass % or less, and more preferably 9 mass % or less, based on 100 mass % of the total amount of the friction material composition. If the content of rock wool is within the above range, the friction coefficient of the friction material during high load braking can be increased.
[0099] (1-5-2.Organic friction modifier) The organic friction modifier is a friction modifier that is blended for the purpose of further improving the noise and vibration performance and wear resistance of the friction material. Examples of the organic friction modifier include unvulcanized or vulcanized rubber powder such as tire rubber, acrylic rubber, isoprene rubber, NBR (nitrile butadiene rubber), SBR (styrene butadiene rubber), chlorinated butyl rubber, butyl rubber, and silicone rubber; cashew dust; rubber-coated cashew dust; melamine dust, and the like. One of these may be used alone, or two or more may be used in combination.
[0100] When the friction material composition contains an organic friction modifier, the content thereof is preferably 0.1 mass % or more, and is preferably 30 mass % or less, more preferably 20 mass % or less, even more preferably 10 mass % or less, and particularly preferably 6 mass % or less, relative to 100 mass % of the total amount of the friction material composition.
[0101] (1-5-3. Inorganic friction modifier) Inorganic friction modifiers are friction modifiers that are blended with the friction material to prevent deterioration of the heat resistance, improve the wear resistance, or further improve the friction coefficient, etc. Examples of inorganic friction modifiers include abrasives, metal powders, and other inorganic fillers.
[0102] The abrasive material can be appropriately selected based on the material of the mating material (such as a disk rotor) so that it acts as an abrasive material to improve the friction coefficient of the friction material, and can be selected based on the Mohs hardness of the mating material.
[0103] Examples of abrasives include silicon carbide, titanium oxide, alpha alumina, gamma alumina, silica (silicon dioxide), magnesia (magnesium oxide), zirconia (zirconium oxide), zircon (zirconium silicate), chromium oxide, iron oxide (iron tetroxide, etc.), chromite, and quartz.
[0104] If the particle size of the abrasive is large, the friction coefficient of the friction material during high load braking can be increased, but the friction coefficient of the friction material during light load braking is not stable. On the other hand, if the particle size of the abrasive is small, the friction coefficient of the friction material during light load braking is stable, but the friction coefficient may be low. For these reasons, an abrasive having a large average particle size and an abrasive having a small average particle size may be used in combination. Specifically, it is preferable to use an abrasive having an average particle size of 0.5 μm to 15 μm in combination with an abrasive having an average particle size of 20 μm to 200 μm. In addition, the mass ratio of the abrasive having a small average particle size to the abrasive having a large average particle size (abrasive having a small average particle size / abrasive having a large average particle size) is preferably 0.1 or more, more preferably 2 or more, and preferably 10 or less, more preferably 8 or less, from the viewpoint of further reducing fine wear dust when used as a friction material.
[0105] When the friction material composition contains an abrasive, the content thereof is preferably 0.1 mass % or more, and preferably 30 mass % or less, more preferably 15 mass % or less, based on 100 mass % of the total amount of the friction material composition.
[0106] The metal powder may be a powder of a single metal or an alloy of aluminum, zinc, iron, tin, etc. One of these may be used alone, or two or more of them may be used in combination.
[0107] Other examples of inorganic fillers include vermiculite, clay, mica, talc, dolomite, chromite, mullite, calcium silicate, etc. Among these, one type may be used alone, or two or more types may be used in combination.
[0108] (1-5-4. Lubricants) The friction material composition of the present invention may further contain other lubricants other than carbon-based solid lubricants and metal sulfide-based solid lubricants. The other lubricants are preferably solid lubricants other than carbon-based solid lubricants and metal sulfide-based solid lubricants, and examples thereof include polytetrafluoroethylene (PTFE). The other lubricants may be used alone or in combination of two or more.
[0109] (1-5-5.pH adjustment material) Examples of the pH adjuster include inorganic bases such as calcium hydroxide (slaked lime), sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, trisodium phosphate, disodium hydrogen phosphate, tripotassium phosphate, dipotassium hydrogen phosphate, and organic bases such as imidazole, histidine, and hexamethylenediamine. From the viewpoint of cost and hygroscopicity, the pH adjuster is preferably an inorganic base. One type of pH adjuster may be used alone, or two or more types may be used in combination. The pH adjuster may also be used to prevent rust adhesion between the friction material and the mating material (such as a disc rotor).
[0110] When the friction material composition contains a pH adjuster, the content of the pH adjuster is preferably 0.1 mass % or more and preferably 8 mass % or less with respect to 100 mass % of the total amount of the friction material composition.
[0111] (1-5-6. Filler) Examples of the filler include barium sulfate and calcium carbonate. The filler is preferably barium sulfate. These fillers may be used alone or in combination of two or more.
[0112] Barium sulfate includes elutriated barium sulfate (baryte powder) obtained by crushing a mineral called barite, washing it to remove iron, and elutriating it, and precipitated barium sulfate which is artificially synthesized. The particle size of precipitated barium sulfate can be controlled by the conditions during synthesis, and fine barium sulfate with a low content of the desired coarse particles can be produced. As barium sulfate, it is preferable to use precipitated barium sulfate from the viewpoint of further reducing impurities and making the particle size distribution of barium sulfate particles more uniform.
[0113] (1-6. Method for producing friction material composition) The friction material composition of the present invention can be produced by, for example, (1) a method of mixing the various components using a mixer such as a Loedige mixer ("Loedige" is a registered trademark), a pressure kneader, or an Eirich mixer ("Eirich" is a registered trademark); or (2) a method of preparing a granule of the desired components and, if necessary, mixing other components using a mixer such as a Loedige mixer ("Loedige" is a registered trademark), a pressure kneader, or an Eirich mixer ("Eirich" is a registered trademark).
[0114] The content of each component in the friction material composition of the present invention can be appropriately selected depending on the desired friction characteristics, and the friction material composition can be produced by the above-mentioned production method.
[0115] The friction material composition of the present invention may be prepared by preparing a master batch containing a specific component at a high concentration, and then adding and mixing the thermosetting resin and the like to this master batch.
[0116] <2. Friction materials and friction components> In the present invention, the friction material composition is preliminarily molded at room temperature (20°C), the obtained preliminarily molded body is heated and pressurized (molding pressure: 10 MPa to 40 MPa, molding temperature: 150°C to 200°C), and if necessary, the obtained molded body is heat-treated in a heating furnace (150°C to 220°C, held for 1 to 12 hours), and then the molded body is machined and polished to produce a friction material having a predetermined shape.
[0117] The friction material of the present invention is used as a friction member formed by forming the friction material to have a friction surface. Examples of friction members that can be formed using the friction material include (1) a structure consisting of only the friction material, and (2) a structure having a substrate such as a backing metal and the friction material of the present invention that is provided on the substrate to provide a friction surface.
[0118] The substrate is used to further improve the mechanical strength of the friction member, and the substrate may be made of a metal, a fiber-reinforced resin, etc. Examples of the metal or fiber-reinforced resin include iron, stainless steel, glass fiber-reinforced resin, and carbon fiber-reinforced resin.
[0119] Friction materials usually have many fine pores formed inside. These many pores serve as escape routes for decomposition products (gases and liquids) at high temperatures, preventing the frictional properties of the friction material from deteriorating, and also reducing the rigidity of the friction material and improving damping properties to prevent squealing. In ordinary friction materials, the material blend and molding conditions are controlled so that the porosity of the friction material is preferably 5% to 30%, and more preferably 10% to 25%.
[0120] The friction member of the present invention is composed of the above-mentioned friction material composition of the present invention, and thus has a composition that is less harmful to the environment and the human body, while generating less fine wear dust such as PM10 and PM2.5. Therefore, the friction member of the present invention can be suitably used in brake systems such as disc brake pads, brake linings (brake shoes), clutch facings, electromagnetic brakes, and holding brakes that constitute braking devices of various vehicles and industrial machines, and can be suitably used as friction members for regenerative brake coordination. In addition, examples of materials for mating members (disc rotors, brake drums, etc.) of the friction member include cast iron, stainless steel, and aluminum, and from the viewpoint of further reducing fine wear dust and further improving friction performance, mating members whose friction surfaces are cast iron or stainless steel can be suitably used. EXAMPLES
[0121] The present invention will now be described in further detail with reference to specific examples.
[0122] The present invention is not limited to the following examples, and can be practiced with appropriate modifications within the scope of the present invention.
[0123] (Example 1 and Comparative Examples 1 to 5) <Manufacture of friction components> The materials were mixed according to the mixing ratios shown in Table 1, and mixed for 3 minutes using an Eirich mixer. The mixture obtained was placed in the cavity of a hot molding die heated to 150°C, and with a back plate (material: steel) placed on top, it was pressurized for 240 seconds at a pressure of 15 MPa to 40 MPa so that the porosity of the resulting molded body would be 15%. The resulting molded body was placed in a constant temperature dryer heated to 210°C and held there for 2 hours to completely harden, thereby obtaining a friction member (disc brake pad).
[0124] [Table 1]
[0125] The materials used in Table 1 are as follows, and the powder properties and the like were measured as follows.
[0126] (Binding material) Phenolic resin: Hexamethylenetetramine-containing novolac-type phenolic resin (straight phenolic resin) powder
[0127] (Steel Fiber) Steel fiber: Curly fiber, average fiber length (cut length) 1.5 mm, average fiber diameter 50 μm, product name "Cut Wool BS-1V", manufactured by Bonstar Sales Co., Ltd.
[0128] (Titanate) The powder physical properties of titanate 1 and titanate 2 are shown in Table 2 below.
[0129] [Table 2]
[0130] (Carbon-based solid lubricant) Graphite: Synthetic graphite powder, average particle size 730μm
[0131] (metal sulfide) Tin sulfide: Tin(II) sulfide powder, average particle size 7μm
[0132] (Other materials) Aramid fiber: fibrillated para-aramid fiber (aramid pulp), fiber length 0.89 mm, specific surface area 9.8 m 2 / g Barium sulfate: Elutriated barium sulfate powder, average particle size 24μm Mica: Natural mica powder, average particle size 180μm Zircon: Zirconium silicate powder, average particle size 1.5 μm Alumina: α-alumina powder, average particle size 57μm
[0133] [Shape, average fiber length, and average fiber diameter of steel-based fibers] The shape was observed using a digital microscope (Keyence Corporation, "VHX-1000") to determine the average fiber length and average fiber diameter. The average fiber length and average fiber diameter were each calculated as the average value of 30 pieces.
[0134] [Titanate particle shape] The particle shape of the titanate was confirmed using a field emission scanning electron microscope (manufactured by Hitachi High-Technologies Corporation, product number "S-4800").
[0135] [Average particle size] The average particle size of each material was measured using a laser diffraction particle size distribution analyzer (Shimadzu Corporation, model number "SALD-2100"), and the particle size at 50% cumulative volume in the obtained particle size distribution was taken as the average particle size. The average particle size of graphite was taken as the average value of 30 particles observed using a digital microscope (Keyence Corporation, model number "VHX-1000"). The average particle size of tin sulfide was taken as the average value of 200 particles observed using a field emission scanning electron microscope (Hitachi High-Technologies Corporation, model number "S-4800").
[0136] [Specific surface area] The specific surface area of each material was measured using an automatic specific surface area measuring device (Micromeritics, product number "TriStarII3020").
[0137] <Evaluation of friction materials> The physical properties of the friction members prepared as described above were evaluated as follows.
[0138] (Rockwell hardness) The Rockwell hardness of the surface of the friction member was measured according to the method of JIS D4421. The S scale was used for the hardness scale.
[0139] (Abrasion dust test) The surface of the friction material was polished by 1.0 mm to prepare a friction material for scale dynamo testing. The friction material and a disc rotor (cast iron rotor belonging to the A type in the ASTM standard) were used to drive the rotor at 65 km / h and 3.5 m / s. 2 The friction members and disc rotors that had been previously fitted under the above conditions were used to carry out an abrasion dust measurement test under the friction conditions in Table 3, and the mass of particulate matter collected by the filter (amount of PM10-2.5 and PM2.5 generated) and the amount of PN generated (number of particles) were measured. The test was carried out twice, and the average value was used as the measurement result.
[0140] [Table 3]
[0141] The results are shown in Table 4 below.
[0142] [Table 4]
[0143] From Table 4, it can be seen that the friction member of Example 1 using the friction material composition containing a binder, steel-based fibers, two or more types of titanates, and a carbon-based solid lubricant, with the steel-based fiber content being 10% by mass or more and less than 30% by mass, and substantially containing no metal sulfide, can reduce the amount of fine wear dust such as PM10 and PM2.5. On the other hand, it can be seen that the friction members of Comparative Examples 1 and 2 using a friction material composition containing only one type of titanate, the friction member of Comparative Example 3 using a friction material composition containing no titanate, and the friction members of Comparative Examples 4 and 5 using a friction material composition containing a metal sulfide cannot sufficiently reduce the amount of fine wear dust.
Claims
1. A friction material composition comprising a binder, steel-based fibers, a titanate, and a carbon-based solid lubricant, The content of the steel fiber in the friction material composition is 10% by mass or more and less than 30% by mass, based on 100% by mass of the total amount of the friction material composition; The copper content in the friction material composition is less than 0.5% by mass in terms of copper element, relative to 100% by mass of the total amount of the friction material composition; The friction material composition contains two or more types of titanates, The friction material composition is substantially free of metal sulfides.
2. 2. The friction material composition according to claim 1, wherein a total content of the two or more types of titanates in the friction material composition is 5% by mass or more and 35% by mass or less, relative to a total amount of the friction material composition (100% by mass).
3. 3. The friction material composition according to claim 1, wherein the two or more kinds of titanates include at least a non-porous titanate (A) and a porous titanate (B).
4. 4. The friction material composition according to claim 3, wherein the titanate (A) is a titanate having a layered crystal structure.
5. 4. The friction material composition according to claim 3, wherein the titanate (A) has an average particle size of 0.1 μm or more and 50 μm or less.
6. 4. The friction material composition according to claim 3, wherein the titanate (B) is a titanate having a tunnel-shaped crystal structure.
7. 4. The friction material composition according to claim 3, wherein the titanate (B) has an average particle size of 50 μm or more and 200 μm or less.
8. 4. The friction material composition according to claim 3, wherein a mass ratio of the titanate (A) to the titanate (B) (titanate (A) / titanate (B)) is 0.1 or more and 12.0 or less.
9. 3. The friction material composition according to claim 1, wherein the content of the carbon-based solid lubricant in the friction material composition is 0.1 mass % or more and less than 15 mass % with respect to 100 mass % of the total amount of the friction material composition.
10. 3. The friction material composition according to claim 1, wherein a mass ratio of the two or more types of titanates to the carbon-based solid lubricant (titanate / carbon-based solid lubricant) is 2.0 or more and 6.0 or less.
11. 3. The friction material composition according to claim 1, wherein the carbon-based solid lubricant is graphite.
12. 3. The friction material composition according to claim 1, wherein the carbon-based solid lubricant has an average particle size of 10 μm or more and 1000 μm or less.
13. 3. The friction material composition according to claim 1, wherein the steel fibers have an average fiber length of 0.1 mm or more and 5 mm or less.
14. A friction material which is a molded product of the friction material composition according to claim 1 or 2.
15. A friction member comprising the friction material according to claim 14.
Citation Information
Patent Citations
Friction material
JP2015059143A
Friction material composition, and friction material and friction member using the same
JP2015147913A
Non-asbestos friction material composition, and friction material and friction member using same
WO2012066968A1
Friction material composition, and friction material and friction member each obtained therefrom
WO2017183155A1